Resist, scientist! Countering degradation rituals in science. (1st June 2014) - Thérèse, Sandrine; Martin, Brian
Abstract : When the work and reputation of scientists suffer ritual degradation, a range of tactics can be deployed to resist and rework the psychological and social impacts. Five key resistance tactics to degradation in science are revealing degradation rituals, redeeming the reputation of the targeted scientist, reframing the degradation as unfair, redirecting attention to other domains, and refusing to cooperate with the rituals. These tactics are illustrated through three case studies of scientists targeted for conducting research threatening to the interests of powerful groups.